The effect of self-resistance electric heating on the interfacial behavior of injection molded carbon fiber/polypropylene composites through molecular dynamics analysis. (20th October 2020) - Zhang, Muhan; Wang, Xiaoyu; Zhou, Mingyong; Zhai, Zhanyu; Jiang, Bingyan
Abstract: The impregnation of carbon fabric reinforcements in an injection mold through self-resistance electric (SRE) heating opens the way for manufacturing carbon fiber reinforced thermoplastics in quantities and low cost. The surface morphology evolution of carbon fiber under SRE heating may affect the interfacial properties of resulting composites. In this work, molecular dynamics was introduced to investigate the atomic-level interaction between carbon fiber (CF) and polypropylene (PP) in composites. The influence of CF surface morphology on the interfacial impregnation ability, mechanical properties and interface failure mechanism were explored. Simulation results reveal that increasing the aspect ratio or the amount of grooves of CF surface can enhance the quality of composite interface. The interface failure mode was found to be related to CF surface morphology. In addition, the high kinetic energy enrichment area was used to predict the evolution of micro-void inside the polymer bulk. Graphical abstract: Image 1 Highlights: Molecular dynamics simulations are performed to study the interfacial properties of CFRT with different fiber surface. Polymer chains especially those close to the fiber surface are highly stretched during the tensile deformation. The grooves on carbon fiber surface have a significant effect on the entanglement of polymer chains at the interface. The high kinetic energy enrichment area can reflect the variation of micro-void inside the polymer.